This is a man’s world: Gendered perceptions of Ugandan agro-input dealers - De, Anusha; Miehe, Caroline; Van Campenhout, Bjorn (International Food Policy Research Institute, 2023)
Esther (a composite of typical experiences) is the proud owner-manager of a small shop in a trading center close to her home in a village in eastern Uganda. With a loan from a savings and credit organization and some help from her husband, she was able to rent a stall and buy sufficient stock to get her business going. She hopes to earn some extra money that can be used to send their children to school, as the income Esther and her husband get from farming is often insufficient and at times uncertain.